Socio-environmental diagnostic of the agricultural productionon the Rabanl paramo (Colombia) as a basisforits agroecological reset (2015)
The paramos are situated in the highest parts of the Andean mountains, between the woods superior limits, and the snow lower layer. In Colombia the paramos are located in the Western, Central and the Eastern mountain ranges, as well as in the Santa Marta Sierra Nevada; they cover a large extension of the country, reaching ther maximum representativeness in the Boyacá departament, where they supply water for the cities and country side aquaducts. The paramo geological, climatic and edaphic characteristics, has attracted the mining development, mainly coal, plus the growing vegetables specially potatos and the establishment of cattle and sheep grazing, over the 300 masl. The relative advantages offered by the natural environment for the develpment of these activities, are in contrast with the soild deterioration suceptibility and whit the great vulnerability of the altoandinos ecosystems, subject to extreme weather conditons, high humidity and steep slopes.The application of agrochemicals and the agricultural forntier expansion are activities that affect negatively the paramo ecosystem, impact the natural resources, the biodivesity, and the water sources. But the country´s current agricultural approach that does not allow to analyze the socio-economic relationships between the population, neither their needs, nor much less teh potential of the fermers settled there. Given this problematc, is intented, under systems approach, and from the socio-economic and environmental assessment, to link the comunity in a participatorymanner, and through senstization strategies, to become masters of their rural reality, by looking for the soil and crop health valuation, and to identify and recognize the existing biodiversity, also the agroecosystem resilience capacity. All ths tacking as a principle the agroecology, in search for a socially viable alternative and envronmentally sustainable in ths today unprotected ecosystem.